THE INFLUENCE OF CUSTOMER REVIEWS, INFLUENCER ENDORSEMENTS ON PURCHASE INTENT BY TRUST IN LOCAL COSMETIC PRODUCTS - Aulia Mirda Saidi; Gilang Pratama Hafidz Gilang (FISIP Universitas Malikussaleh, 2026)
Beauty and care are no longer luxuries but necessities, so awareness of the importance of cosmetic products in everyday life is increasing, especially among women. This study aims to explore the influence of the relationship between customer reviews and influencer endorsements on purchase intention and actual purchase, moderated by trust, in local cosmetic products. The research method used is descriptive causality, with a quantitative approach and purposive sampling. Primary data were collected from 128 respondents who use local cosmetic products and are domiciled in Greater Jakarta (Jabodetabek) via an online questionnaire. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results of this study indicate that customer reviews and influencer endorsements positively affect purchase intention. Customer reviews positively affect purchase intention, with trust moderating this effect. Influencer endorsements positively affect purchase intention, with trust moderating this effect. Purchase intention positively affects actual purchase. The managerial implications of this study highlight the importance of customer reviews and influencer endorsements in increasing purchase intention, actual purchase, and trust, through transparency, product quality, and effective marketing strategies. It is recommended that future research consider the cultural context to understand the influence of customer reviews and influencer endorsements on consumer behavior of local cosmetic products.